2017
DOI: 10.26226/morressier.594bbebed462b8028d893d2d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recent trends in burn epidemiology worldwide: a systematic review.

Abstract: Burn injuries have been more prevalent among low socioeconomic populations and in less developed regions. Incredible advances in burn care and social development over the recent decades, however, should have placed the incidence and severity of burns in a downwards trend. The aim of this review was to give an overview on current trends in burn epidemiology across the world. Also the socioeconomic development in countries that have published epidemiological data used in this study has been taken into account wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 43 publications
5
60
0
7
Order By: Relevance
“…But this data is true only for low and low middle income country for high income country it is the males who are more affected. A systematic review done by Smolle et al (2017) 22 which included the data mostly of high income countries found the mean male:female ratio of all studies together was 1.92:1. The TBSA(Total Body Surface Area) burn group were mostly between 0 and 20%.This result Acinetobacter is increasingly recognized as a significant healthcareassociated, opportunistic and multidrug-resistant pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…But this data is true only for low and low middle income country for high income country it is the males who are more affected. A systematic review done by Smolle et al (2017) 22 which included the data mostly of high income countries found the mean male:female ratio of all studies together was 1.92:1. The TBSA(Total Body Surface Area) burn group were mostly between 0 and 20%.This result Acinetobacter is increasingly recognized as a significant healthcareassociated, opportunistic and multidrug-resistant pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…Sebuah studi serupa tentang perkembangan manajemen luka bakar telah dilakukan, tetapi hanya mengevaluasi populasi Eropa. 1,2 Manajemen nyeri untuk luka bakar merupakan bagian yang tidak terpisahkan dari manajemen luka bakar yang berhubungan dengan proses penyembuhan luka bakar itu sendiri. Penelitian manajemen nyeri pernah dilakukan di RSUP Dr. Hasan Sadikin tahun 2017, menggambarkan efektivitas pemberian analgetik pada nyeri akut selama tahun 2017 didapatkan angka sebesar 70,3%.…”
Section: Pendahuluanunclassified
“…Severe and large skin burns cause structural and functional pathological changes in all organs and systems of burned persons, which initiates the development of burn disease [14], a disease that has become increasingly widespread in recent years [9,26].…”
Section: Introductionmentioning
confidence: 99%